Chomsky's Question of Innateness and Language Acquisition Acceptance and Disapproval (مجلة ديالى للبحوث الانسانية, 2022)
A whole new subdiscipline has developed in recent years called psycholinguistics . This can be seen as the intersection between psychology and linguistics. It has also some relation with logic and the philosophy of language . It links also with neurolinguistics ( the study of the neurological basis for language) . The above discipline tries to show the relation between throught , mind and language. The conception of the relationship of thought , language and speech is clearly a mentalistic one . A ccording to that conception , a person is regarded as having mind that is distinct from that person's body . Body and mind are seen as interacting with one another.